Building retrofit solutions in the context of energy resilience and urban environment regeneration - Croitoru Cristiana; Calotă Răzvan; Lemian Diana; Civiero Paolo; Aelenei Laura (E3S Web of Conferences)
This paper highlights the role of building retrofitting in developing energy-resilient communities as a part of sustainable urban regeneration. Different approaches and technologies are covered, with the role of improving the energy performance of existing buildings by utilizing, among others, innovative insulation materials or renewable sources for heat supply combined with advanced smart control systems. The case studies from different parts of the world illustrate that this techno-economically viable retrofitting approach can reduce around 40 % energy consumption and emissions, making buildings more sustainable. The analysis of the new economic and regulatory is connected with the government’s incentives as well as public engagement in developing positive energy communities. This paper also documents an extensive evaluation of retrofit technologies and their application, demonstrating the critical contribution energy retrofits can make towards achieving enduring urban sustainability.